The effect of an intervention for organizing primary mental health care in Brazil: a study based on routine process indicators - Ilana Eshriqui; Letícia Yamawaka de Almeida; Joana Moscoso Teixeira de Mendonça; Leandro Anazawa; Lorrayne Belotti; Sandra Fortes; Ana Alice Freire Sousa; Evelyn Lima de Souza; Claudielle de Santana Teodoro; Daiana Bonfim; Joel de Almeida Siqueira Junior; Antonio Cleilson Nobre Bandeira; et al. (BMC Primary Care, 2025)
Abstract Background The “Mental Health Care in Primary Health Care (PHC)” project (SMAPS, from Portuguese) was developed in six health regions from three Brazilian states. Considering the gap and relevance of monitoring and assessing mental health (MH) care in real-world settings using data from service records, this study aimed to evaluate the effect of SMAPS on indicators of MH care process in PHC, calculated from official records available in health services. Methods This is a pilot study conducted between January 2022 and September 2023. The sample comprised 18 PHC units in 14 municipalities, which were in one of the three Brazilian states that adhered to SMAPS and assigned to one of two groups: control and intervention (2:1). Secondary data were collected at two times using the same instrument to systematize the retrieval of aggregated data, which were extracted from management reports from PHC units or municipalities departments. Data analysis was performed using descriptive statistics at the PHC units or municipality level. Results The rate of referrals to MH specialties per consultation with a MH classifications record seemed to decline in intervention and control group. The percentage of benzodiazepine medications delivered for PHC decreased from 16.1 to 11.3% in the intervention group municipalities but increased from 20.3 to 24.1% in the control group. An inverse pattern was observed for antipsychotic, anticonvulsant, and antidepressant medications (increased from 82.2 to 86.2% in the intervention group municipalities and declined from 77.6 to 74.4% in the control group). Despite this, analyzing the mean variation in MH care indicators, statistically significant differences between groups in distribution at the 5% level were not identified. Conclusion The present pilot study points to possible effects of SMAPS for organizing MH care in PHC, especially regarding the referrals to specialty mental health care and the delivery of psychotropic medications. It contributes to the formulation of proposals for evaluating MH care based on data already available from records and reports from health services and emphasizes the need to improve the quality of MH care recording in PHC work routines.